Case report: Lymphocytic-plasmacytic and eosinophilic enterocolitis presented with marked eosinophilia and basophilia in a cat - Kim, Jin-Young; Hwang, Tae-Sung; Jung, Dong-In; Song, Kun-Ho; Song, Joong-Hyun (Frontiers in Veterinary Science, 2023)
Inflammatory bowel disease is a common condition in cats, characterized by recurring gastrointestinal signs with histologic evidence of intestinal inflammation. A 9-month-old neutered male Sphynx cat was presented with a 5-week history of vomiting and hematochezia. Conservative patient management with a therapeutic gastrointestinal formula, antibiotics, and antiemetics resulted in a positive response to treatment, with relapse of signs when the medications were discontinued. A new finding of marked eosinophilia and basophilia was identified 3 months after the initial presentation. Colonoscopy revealed cecal erosions and a surgical biopsy with histopathology confirmed a diagnosis of lymphocytic-plasmacytic and eosinophilic enterocolitis. For this diagnosis, the patient was treated with prednisolone, tylosin, and metronidazole. Antibiotics were gradually tapered as the cat showed clinical improvement. The patient showed resolution of the gastrointestinal signs, and the numbers of eosinophils and basophils returned within the reference range 8 weeks after the treatment began. Basophilia and eosinophilia has been reported in conjunction with feline T-cell lymphoma. However, marked basophilia accompanying eosinophilia is extremely rare in cats with inflammatory bowel disease. We herein provide clinical details, including ultrasonography, endoscopy, histopathology, and disease course of feline lymphocytic-plasmacytic and eosinophilic enterocolitis with marked basophilia and eosinophilia. This case highlights the importance of considering enteritis as potential diagnoses when eosinophilia and basophilia are concurrently observed in cats.